2007
DOI: 10.1007/s11430-007-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Artificially triggered lightning and its characteristic discharge parameters in two severe thunderstorms

Abstract: The lightning-induced-damages in the mid-latitude regions are usually caused during severe thunderstorms. But the discharge parameters of natural lightning are difficult to be measured. Five lightning flashes have been artificially triggered with the rocket-wire technique during the passage of two severe thunderstorms. The discharge current and close electric field of return stroke in artificially triggered lightning have been obtained in microsecond time resolution by using current measuring systems and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 21 publications
(34 reference statements)
1
26
0
Order By: Relevance
“…The regression equation for 143 triggered-lightning strokes as given by Schoene et al [2009] is I peak = 12.3 Q 1 ms 0.54 (R 2 = 0.76) and the regression equation for Berger's 89 natural-lightning first strokes is I peak = 10.6 Q 1 ms 0.7 (R 2 = 0.59). Qie et al [2007] reported I peak = 18.5 Q 1ms 0.65 for ten triggered-lightning strokes in China. [6] In this paper, we compare the peak currents of the lightning return strokes with the corresponding charges transferred during various time intervals within 1 ms after return stroke initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The regression equation for 143 triggered-lightning strokes as given by Schoene et al [2009] is I peak = 12.3 Q 1 ms 0.54 (R 2 = 0.76) and the regression equation for Berger's 89 natural-lightning first strokes is I peak = 10.6 Q 1 ms 0.7 (R 2 = 0.59). Qie et al [2007] reported I peak = 18.5 Q 1ms 0.65 for ten triggered-lightning strokes in China. [6] In this paper, we compare the peak currents of the lightning return strokes with the corresponding charges transferred during various time intervals within 1 ms after return stroke initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The risetime (RT) of lightning current is assumed to be 5h/c. Note that, when the lightning strikes the 50-m-tall object, RT is about 0.8 μs (5h/c), a typical subsequent return stroke with relatively more high frequency (e.g., Qie et al, 2007Qie et al, , 2009Qie et al, , 2014Wang et al, 2012;Yang et al, 2008Yang et al, , 2010Zhang et al, 2009), the corresponding field attenuation along the finitely conducting ground is more (see Fig. 6(b)), because the presence of tall objects tends to further increase higher frequency contents, and the field propagation attenuation for lighting strike to tall objects mainly depends on the height of tall objects, the earth conductivity and the current RT.…”
Section: Results and Analysismentioning
confidence: 99%
“…Expressions relating radiated fields and return stroke channel base currents have been derived for various "engineering" return stroke models (Rakov and Uman, 1998 ). Based on the transmission line (TL) model, for an observation point at ground level, the radiated (far) electric and magnetic fields produced by a vertical lightning channel terminated directly at ground are simply proportional to the channel base current (Uman et al, 1975;Qie et al, 2007Qie et al, , 2009Qie et al, , 2011Yang et al, 2010), with the proportionality coefficient being determined for strike to flat ground with the perfect conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…We found no known solutions to integrals of this form, and therefore the return stroke electric and magnetic fields cannot be written in closed form and must be solved for numerically. Figure 6 (b) and (d) shows electric field emissions at 60 m and 550 m of leader and return strokes from rocket triggered lightning experiments from [3] compared with the TG model (a) and (c). These data show many of the same features evident in the 100 m and 1000 m modeled data.…”
Section: The Lightning Return Strokementioning
confidence: 99%